2010
DOI: 10.1128/aem.00671-10
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Norovirus: Carbohydrate Ligand, Environmental Contamination, and Potential Cross-Species Transmission via Oysters

Abstract: Noroviruses (NoV) are major agents of acute gastroenteritis in humans and the primary pathogens of shellfish-related outbreaks. Previous studies showed that some human strains bind to oyster tissues through carbohydrate ligands that are similar to their human receptors. Thus, based on presentation of shared norovirus carbohydrate ligands, oysters could selectively concentrate animal strains with increased ability to overcome species barriers. In comparison with human GI and GII strains, bovine GIII NoV strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…The removal of virus by treatment was 52% and 79% for GI and GII HuNoV, respectively. These results are representative of the results of numerous studies reporting detection of HuNoV in treated-sewage effluent samples (3,9,11,17,35,39). These reports raise concern in public safety, since HuNoV is highly infectious with Ͻ10 virus particles capable of causing disease (32).…”
supporting
confidence: 70%
“…The removal of virus by treatment was 52% and 79% for GI and GII HuNoV, respectively. These results are representative of the results of numerous studies reporting detection of HuNoV in treated-sewage effluent samples (3,9,11,17,35,39). These reports raise concern in public safety, since HuNoV is highly infectious with Ͻ10 virus particles capable of causing disease (32).…”
supporting
confidence: 70%
“…Similar to results of a previous study (13), significant reduction of TV replication in LLC-MK2 cells was seen after treatment of TVs with the A type 3 and B antigens. As an analogy, we predict that human HBGAs or a carbohydrate receptor also plays an important role in the replication of human NoVs and related caliciviruses (26)(27)(28)(29). To look into the report of increased TV infectivity by type A and B oligosaccharides in an earlier study (13), we carefully evaluated the experimental procedures described in the study and identified a potential problem that could cause a false result.…”
Section: Discussionmentioning
confidence: 99%
“…NV) persisted in oysters while feline calicivirus were eliminated over 10-day depuration, reinforcing the existence of selective mechanisms driving specific virus binding to oyster tissues (Ueki et al 2007). A recent report suggested that this selective retention of NV may drive cross-species transmission to humans of viral genotypes abler to accumulate in shellfish tissues (Zakhour et al 2010). …”
Section: )mentioning
confidence: 99%